PENGARUH ETOS KERJA, PERILAKU, DAN KOMPENSASI TERHADAP KOMITMEN HAFIZH DAN HAFIZHAH PONDOK PESANTREN AHLUL–QUR’AN DAN AL–LATHIFIYYAH PALEMBANG - Sobirin Sobirin; Fakhry Zamzam; Luis Marnisah (Ekonomica Sharia: Jurnal Pemikiran dan Pengembangan Ekonomi Syariah, 2020)
The objective of this research was specifically to get a analysis result of the effect of work ethic, behavior and compensation variables on the commitment of Hafizh and Hafizhah Ahlul Qur'an and Al-Lathifiyyah Islamic Boarding Schools partially or simultaneously. This research was associative research, where in this research there were variables that were related and affected other variables. The research population was 106 people and the sample was 87 people. The data was calculated by using SPSS tools. The coefficient of determination effect of the work ethic on commitment was 0.390 or 39,%. The coefficient of determination effect of the work ethic towards commitment was 0.242 or 24.2%. The coefficient of determination of the effect of compensation on commitment was 0.006 or 0.061%. This research findings did not confirm between the field theory and conditions that appropriate and effective compensation would affect commitment. The red line of this research was Work Ethics and Behavior simultaneously affected the commitment of Hafizh and Hafizhah at the AhlulQur'an and Al-Lathifiyyah Islamic Boarding Schools while the effect of compensation on commitment had not been confirmed through this research.